Cellular Therapy for Stroke and CNS Injuries - Zhao, Li-Ru; Zhang, John H. (Springer Series in Translational Stroke Research, 2015)
The first book to focus on cellular therapy for stroke and other CNS injuries. Addresses recent research on all relevant cell types including neural stem cells, bone marrow stem cells, endothelial progenitor cells, and many others that have had protective or regenerative effects in animal models. Cellular therapy for stroke and neural trauma has gained worldwide attention during the last decade and has shown some promising results. The book also provides information on cell isolation and culture skills, transplantation methods, and neurological functional evaluations.  .